Description of Participatory Leadership Style on The Performance of The Accompanying Teacher for The Millennial Type at The Darul Hikam Male Student Dormitory - Hendar Priatna (Journal of Education and Counseling (JECO), 2020)
Performance of Milenieal Guardian type is held for 7 months in Dormitory Putera Darul Hikam, Jl. Dago Giri Lembang regency of West Java. Objectives This scientific article illustrates the application of participative leadership process and its effect on the performance of the Teacher Boardinger of Darul Hikam son of the Y (Milenial) work force. The process of data retrieval using daily observation methods conducted directly by the boarding house and ended with a filling questionnaire satisfaction by foster parent. The data is processed using Excel software to produce the average value. Based on the research that has been implemented, it can be concluded that the participative leadership style applied in Darul Hikam Boarding House is in accordance with the character and able to improve the performance of foster mother millenial generation.